Risk factors for substances use and misuse among young people in France: What can we learn from the Substance Use Risk Profile Scale?. (1st June 2016) - Ali, A.; Carré, A.; Hassler, C.; Spilka, S.; Vanier, A.; Barry, C.; Berthoz, S.
Highlights: The SURPS measurement invariance was confirmed across gender and three age bands. Hopelessness, Impulsivity and Sensation Seeking are risk factors for drug-use. Anxiety Sensitivity is a protective factor for Alcohol, Tobacco and Cannabis use. There exist genuine differences on personality scores between boys and girls. Interactions between personality traits and gender should always be investigated. Abstract: Background: The prevention of addictions in young people is a challenge for Mental and Public Health policies, and requires specific risk-screening tools. Specific personality traits, as assessed using the Substance Use Risk Profile Scale (SURPS), could play a key role in the onset and escalation of substance use. This study aimed to examine (1) measurement invariance across age and gender (2) the effects of age and gender on associations between SURPS scores and the most frequently-consumed substances. Methods: Analyses were based on the responses from 5069 participants (aged 14–20 years) from the 2011 ESPAD-France dataset. Substance-use outcomes were experimentation and current frequency of alcohol, tobacco and cannabis use, and drunkenness. Results: Our approach, consisting in analysing measurement and structural invariance and interaction terms, established the stability of (i) SURPS profiles, and (ii) relationships between these scores and substance experimentation and use over a developmental period ranging from mid-adolescence to early adulthood. Measurement invariance across genders was also confirmed despite the absence of scalar invariance for 2 items. Significant interactions between gender and SURPS factors were established, highlighting differential vulnerability, especially concerning Hopelessness and experimentation of alcohol and drunkenness, or Impulsivity and tobacco experimentation. Finally, Anxiety Sensitivity could be protective against substance use, especially for cannabis in girls. Conclusions: Our results suggest the relevance of the SURPS to assess vulnerability towards drug use, and underline the need to consider gender differences in addiction risks.